2019
DOI: 10.1101/510131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel defective recombinant porcine enterovirus G virus carrying a porcine torovirus papain-like cysteine protease gene and a putative anti-apoptosis gene in place of viral structural protein genes

Abstract: 35Enterovirus G (EV-G) belongs to the family of Picornaviridae. Two types of recombinant porcine 36 EV-Gs carrying papain-like cysteine protease (PLCP) gene of porcine torovirus, a virus in 37 Coronaviridae, are reported. Type 1 recombinant EV-Gs are detected in pig feces in Japan, USA, 38 and Belgium and carry the PLPC gene at the junction site of 2C/3A genes, while PLPC gene 39 replaces the viral structural genes in type 2 recombinant EV-G detected in pig feces in a Chinese 40 farm. We identified a novel ty… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…The sequence of PToV‐ZJU39 reported in the current work is only the sixth complete PToV genome sequence to have been reported thus far, which greatly limits our exploration of the origin and evolution of PToV. Inter‐order recombination between ToV (order Nidovirales ) and the order Picornavirales was recently discovered in different geographical locations (Imai et al., 2019; Ito et al., 2016; Knutson et al., 2017; Lee & Lee, 2019; Shang et al., 2017; Smits et al., 2003; Wang et al., 2018), which further supports the idea that PToVs are common in swine populations globally, along with other enteric pathogens.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The sequence of PToV‐ZJU39 reported in the current work is only the sixth complete PToV genome sequence to have been reported thus far, which greatly limits our exploration of the origin and evolution of PToV. Inter‐order recombination between ToV (order Nidovirales ) and the order Picornavirales was recently discovered in different geographical locations (Imai et al., 2019; Ito et al., 2016; Knutson et al., 2017; Lee & Lee, 2019; Shang et al., 2017; Smits et al., 2003; Wang et al., 2018), which further supports the idea that PToVs are common in swine populations globally, along with other enteric pathogens.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, PToV has received increasing attention due to evidence of inter‐order recombination between PToV and porcine enterovirus G (EV‐G; order Picornavirales ) in different geographical locations. Porcine EV‐G genomes were detected with an insertion of PToV papain‐like cysteine protease gene at the 2C/3A junction in the faeces of diarrhoeal pigs from farms in the United States, Belgium, Japan, China and South Korea (Conceicao‐Neto et al., 2017; Imai et al., 2019; Knutson et al., 2017; Lee & Lee, 2019; Shang et al., 2017; Wang et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, including ours, have reported the presence of recombinant type 1 EV-G in many different countries worldwide [6,8,15,17,20,35,40,42]. Type 1 recombinant EV-G has an insertion of a papain-like cysteine protease (PLCP) gene of the porcine torovirus genome at the 2C-3A junction sites [40].…”
Section: Introductionmentioning
confidence: 75%
“…In addition to type 1 recombinant EV-Gs, type 2 recombinant EV-G genomes that carry an insertion of a torovirus PLCP gene with long flanking genes (unique region 1 [Un1] and unique region 2 [Un2]), in place of viral structural genes have been reported [15]. Amino acid alignment indicated that the biological functions of the PLCP of most type 2 recombinant EV-Gs may be similar to those of the PLCP of type 1 recombinant EV-Gs [15].…”
Section: Introductionmentioning
confidence: 99%
“…Their HE, which is related to haemagglutinin-esterase-fusion (HEF) protein of influenza C, and PDE are thought to have been independently obtained from these ancestors by heterologous recombination events ( Figure 2 ) [ 92 ]. Remarkably, heterologous recombination between ToV and picornavirus has been discovered recently in many countries; a ToV-like PL pro gene is inserted into the porcine enterovirus G (EV-G) genome at the 2C/3A junction [ 93 , 94 , 95 , 96 , 97 ] or completely replaces a viral structural gene up to the VP1/2A junction [ 98 , 99 ] ( Figure 3 c), suggesting that ToV-like PL pro benefits the growth of EV-G.…”
Section: Genomementioning
confidence: 99%